The effect of xylazine on Clinical Symptoms and Hemato- Biochemical Parameters in Dogs (Journal of Hama University, 2019)
The Present study was designed to evaluate the  effect  of  xylazine 2% on some elements and Biochemical of Dogs blood and record some vital reflexes (Heart rate ,analgesic, absence of sensory reflexes ,Respiratory rate and body temperature) which appear in dogs during injection and after injection.                                                                                                     For this Purpose ,six local breed  dogs  of about  6-8 kg body weight(male) and Aged between 2-4 years where blood samples were taken before injection then all dogs were injected intravenously with xylazine 2%. After that  blood samples were taken after 15,30,60,120 minutes and after 24 hours. Then sensory reflexes are recorded according  to previous intervals.            As a result , heart rate ,respiratory rate and body temperature showed significant decrease (P